Analysing Muslim traditions : studies in legal, exegetical and Maghazi hadith - Motzki, Harald. (Islamic History and Civilization, 2010)
Since its inception, the study of Ḥadīth conducted by scholars trained in the Western academic tradition has been marked by sharp methodological debates. A focal issue is the origin and development of traditions on the advent of Islam. Scholars' verdicts on these traditions have ranged from "late fabrications without any historical value for the time concerning which the narrations purport to give information" to "early, accurately transmitted texts that allow one to reconstruct Islamic origins". Starting from previous contributions to the debate, the studies collected in this volume show that, by careful analysis of their texts and chains of transmission, the history of Muslim traditions can be reconstructed with a high degree of probability and their historicity assessed afresh.